Development of STEM-Based Digital Handouts for Nuclear Physics Introduction Courses During the Covid-19 Pandemic - Murniati Murniati; Apit Fathurrohman; Yurindah Letari (Jurnal Penelitian Pendidikan IPA, 2022)
The Covid-19 pandemic has caused changes in the world educational system. The pandemic caused a rapid transition from face-to-face lectures to online lectures. The times of the Covid-19 pandemic or what is often called “the New Normal", are still ongoing today. Online lectures are expected not to reduce the Program Studi’s Graduate Learning Outcomes (GLO) of a course or not to reduce competencies that must be mastered by students. Lecturers as course supervisors must try to facilitate the student learning process with valid, and easy-to-use teaching materials. To meet the needs of these students, first, we must know the student's responses to the teaching materials, so that it can facilitate independent learning in students during these pandemic times. This research is developmental research that aims to produce digital handouts that can be accessed via cellphones or laptops and can be accessed both online and offline situations. The development model chosen in this research is the Rowntree model with Tessmer formative evaluation. The data was obtained through online questionnaires created in the google form and given to lecturers or students. The results showed that 100% of students had difficulties in learning nuclear physics introduction materials independently and 86% of them requested that the teaching materials should be provided with pictures, animations, and videos. Based on the needs analysis above, we develop a valid and practical STEM-based digital handout teaching materials about nuclear physics introduction